The Development Trend of Belt and Road Initiative in Egypt - Wu, Shuang; Machmudi, Yon (Journal Of Middle East and Islamic Studies, 2024)
This article discusses three main points: First, Egypt occupies an undoubted central position in the Arab world. Second, in addition to its great regional influence, Egypt also occupies an important geographical position. Egypt is located on the two continents of Europe and Asia, and the Suez Canal in it is an important energy channel for the Indian Ocean to enter Europe and the Mediterranean. Third, China and Egypt have a history of friendly exchanges. Since the drastic changes in the Middle East in 2011, Egypt's national power has gradually weakened. To achieve economic development and social stability, Egypt urgently needs foreign investment. The proposed Belt and Road Initiative provides new development opportunities for China-Egypt cooperation. This article uses literature analysis and case analysis. The result of the study is that close economic cooperation between China and Egypt has promoted Egypt's overall positive development, but political cooperation and cultural exchanges between the two countries still need to be strengthened.